Identity Development of Foreign Language Teachers in Lithuania - Mastandrea, Adam; Palaimaité, Gabrielé (Verbum, 2021)
Teacher identity is an evolving, multi-dimensional concept of a teacher’s understanding of self, best understood as a dynamic narrative of self-growth. The present study is focused on hypothesized stages of teacher identity development (Pride, Survival, Experimentation, Disenchantment, Rebellion and Progressive Proficiency) and their occurrence in Lithuanian foreign language teachers. A series of semi-structured interviews were carried out with eight Lithuanian foreign language teachers to discover their personal narratives of teacher identity development.The findings of the qualitative case study research revealed that key features of the six possible identity stages were present across the unique experiences of theforeign language teachers interviewed. However, each research participant displayed only certain key features of each identity development stage rather than a combination of all the possible features. In general, less experienced teachers displayed fewer key features at certain identity stages, implying that they had not experienced particular phases of identity development to completion. The results suggest certain features of identity development stages can be omitted and then experienced later in a teacher’s career. Teacher satisfaction with compensation, job security, professional prestige and the education system in general were additional factors that contributed uniquely to the identity development of teachers working in Lithuania.
Keywords: Teacher research; teacher identity development; foreign language teaching in Lithuania